AN ANALYSIS OF TEACHER TEACHING STRATEGIES USED TO MOTIVATE STUDENTS IN LEARNING ENGLISH VOCABULARY - Ervina Azisa; Sahril Sahril; Abdullah Abdullah; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to identify the teaching strategies used by teacher in motivating students to learn English vocabulary. The subject of this research is an English teacher at SMPN 51 Makassar. This research used descriptive qualitative method. The data of this research were collected through observations, interview, and documentations. The data obtained was analyzed using four stages: data collection, data condensation, data display, and drawing conclusion. The results of this research show that there are six teaching strategies used by teacher in teaching students’ English vocabulary, namely: using translation, games, guessing from context, making tasks, memorizing, and using pictures.